HOSPITAL- AND COMMUNITY- BASED SURVEILLANCE OF ZIKA AND DENGUE VIRUSES IN INDONESIA - Suharto, Nasronudin; Amin, Muhammad; Rini, Diah Puspita; Romdhoni, Achmad Chusnu; Pawanis, Purwaningsih Zulfayandi; Hidayat, Muhammad Syamsul (African Journal of Infectious Diseases (AJID), 2017)
Background: Zika virus remained silent for few decades after its first recognition in 1947. Recently, Zika drew global attention due to the outbreak in Pacific island and Latin Americas. The concern was escalating given the shared vector of Zika and dengue with possible deleterious complications. Surabaya as one of the largest cities in Indonesia with high mobility of people is endemic to dengue. This study was aimed to detect Zika infection during dengue outbreaks in Surabaya. Materials and Methods: This was a surveillance study involving patients visiting 4 public hospitals and 8 primary health care centres (PHCs). Patients were recruited if they were suspected to have dengue infection based on WHO guidelines (1997). The recruitment was based on the attendance of the patients at the healthcare facilities until the maximum quota was fulfilled. Dengue serological diagnostic confirmation was based on non-structural protein 1 (NS1) and/or immunoglobulin M (IgM) detection. Zika virus infection was examined using real time polymerase chain reaction (RT-PCR) test. Results: Between February and April 2016, 100 patients consented to participate in this study - 54 females and 46 males. Furthermore, 55 patients were recruited from PHCs and the other 45 patients were from hospitals. Median age was (median (IQR)) 28.6 (14.6) years (range15 to 65 years). Of 100 patients examined, there was no Zika infection detected, but 11 patients were identified to have positive dengue infection with varying clinical and laboratory presentations. Conclusion: Serosurveillance of Zika and dengue infection in Surabaya City found no evidence of Zika infection among those presented to healthcare facilities.